Le travail du bois de cerf à Villeparisis (Seine-et-Marne) : un dépotoir au sein d’un atelier de potiers du Bas Empire - Isabelle Rodet-Belarbi; Franck Mallet (Revue Archéologique du Centre de la France)
The excavations, in Villeparisis’ town centre (Seine-et-Marne) led in 2003 and 2005, have revealed a large craft area occupied during the Late Romantimes. The remains of a potter’s workshop and 60 red deer antlers have been discovered. These are incomplete and show many traces of work. Their analysis dœs no enable us to determine which artefacts had been made.